Pemanfaatan Media Sosial Komunitas Untuk Menghadapi Konten Islam Ekstrim Di Internet - Arini Indah Nihayaty; Atikah Mardhiya Rohmy (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
Terrorism and radicalism, in the name of religion, which in nature deconstruct the development of the existing state, must be completely eliminated. Moreover, if terrorism and radicalism, by making social media a means of recruiting members. If so, the policy makers must intervene and make a stronghold in the digital space. In addition, there must be a step from the community exponents to participate in combating terrorism and radicalism. For example, from Islamic boarding schools and Islamic community organizations, such as Nahdlatul Ulama or NU and Muhammadiyah, in Indonesia. The existence of NU and Muhammadiyah is central because so far, they have played a role in advancing the nation from all fronts. The activeness of these two community organizations in counter movement, dealing with terrorism and radicalism is a must. Ways that can be taken include da’wah or the spread of positive messages through social media. What is aggressively done through time and space. Keywords: Da'wah, Social Media, Terrorism, Radicalism